Interrupted versus continuous suture technique for biliary-enteric anastomosis: randomized clinical trial. Issue 1 (1st February 2023) - Seifert, Lena; von Renesse, Janusz; Seifert, Adrian M; Sturm, Dorothée; Meisterfeld, Ronny; Rahbari, Nuh N; Kahlert, Christoph; Distler, Marius; Weitz, Jürgen; Reissfelder, Christoph
Abstract: Background: Biliary-enteric anastomosis (BEA) can be performed using continuous or interrupted suture techniques, but high-quality evidence regarding superiority of either technique is lacking. The aim of this study was to compare the suture techniques for patients undergoing BEA by evaluating the suture time as well as short- and long-term biliary complications. Methods: In this single-centre randomized clinical trial, patients scheduled for elective open procedure with a BEA between 21 January 2016 and 20 September 2017 were randomly allocated in a 1:1 ratio to have the BEA performed with continuous suture (CSG) or interrupted suture technique (ISG). The primary outcome was the time required to complete the anastomosis. Secondary outcomes were BEA-associated postoperative complications with and without operative revision of the BEA, including bile leakage, cholestasis, and cholangitis, as well as morbidity and mortality up to day 30 after the intervention and survival. Results: Altogether, 82 patients were randomized of which 80 patients received the allocated intervention (39 in ISG and 41 in CSG). Suture time was longer in the ISG compared with the CSG (median (interquartile range), 22.4 (15.0–28.0) min versus 12.0 (10.0–17.0) min, OR 1.26, 95 per cent c.i. 1.13 to 1.40; unit of increase of 1 min; P < 0.001). Short-term and long-term biliary complications were similar between groups. The incidence of bile leakage (6 (14.6 per cent) versus 4 (10.3 per cent), P = 0.738) was comparable between groups. No anastomotic stenosis occurred in either group. Conclusion: Continuous suture of BEA is equally safe, but faster compared with interrupted suture. Registration number: NCT02658643 (http://www.clinicaltrials.gov ). Abstract : A randomized clinical trial comparing the benefits and risks of continuous and interrupted suture techniques for patients undergoing biliary-enteric anastomosis showed no differences for short-term and long-term biliary complications. Suture time for biliary-enteric anastomosis was significantly reduced in the continuous suture group compared with the interrupted suture group.